Water Ingress in Encapsulated Inverted Organic Solar Cells: Correlating Infrared Imaging and Photovoltaic Performance. Issue 20 (12th August 2015) - Adams, Jens; Salvador, Michael; Lucera, Luca; Langner, Stefan; Spyropoulos, George D.; Fecher, Frank W.; Voigt, Monika M.; Dowland, Simon A.; Osvet, Andres; Egelhaaf, Hans‐Joachim; Brabec, Christoph J.
<x xml:space="preserve">Abstract</x> Understanding the degradation and failure mechanisms of organic photovoltaic devices is a key requirement for this technology to mature toward a reliable product. Here, an investigation on accelerated temperature and moisture long‐term stability testing (>20 000 h) of inverted and glass‐encapsulated poly(3‐hexylthiophene)/phenyl‐C61‐butyric acid methyl ester solar cells is presented. The degradation kinetics is analyzed using the Arrhenius model and the resulting activation energy for the diffusion of water is measured to be ≈43 kJ mol−1. Through comparison of electroluminescence imaging, lock‐in thermography, and photoluminescence mapping, the device performance is correlated with the loss of effective cell area and it is shown that the reaction of water at the hole extraction/active layer interface is likely to be the dominant cause for long‐term device failure. The diffusion of water through the packaged solar cell is described using classical diffusion theory. Based on an analytical solution of a simple diffusion model, the diffusion coefficient is estimated to be 4 × 10−12 m2 s−1. A shelf life of 100 000 h is anticipated at 65 °C/85% RH using a 9.3 cm wide protective adhesive rim. The findings of this study may inform strategies for predicting lifetimes of organic solar cells and modules based on local in situ tracking of moisture‐induced device performance loss using IR imaging.